Reliable environmental trace heavy metal analysis with potentiometric ion sensor - reality or a distant dreams - Lisak, Grzegorz (2022)
Over two decades have passed since polymeric membrane ion-selective electrodes were found to exhibit sufficiently lower detection limits. This in turn brought a great promise to measure trace level concentrations of heavy metals using potentiometric ion sensors at environmental conditions. Despite great efforts, trace analysis of heavy metals using ion-selective electrodes at environmental conditions is still not commercially available. This work will predominantly concentrate on summarizing and evaluating prospects of using potentiometric ion sensors in view of environmental determination of heavy metals in on-site and on-line analysis modes. Challenges associated with development of reliable potentiometric sensors to be operational in environmental conditions will be discussed and reasoning behind unsuccessful efforts to develop potentiometric on-site and on-line environmental ion sensors will be explored. In short, it is now clear that solely lowering the detection limit of the ion-selective electrodes does not guarantee development of successful sensors that would meet the requirement of environmental matrices over long term usage. More pressing challenges of the properties and the performance of the potentiometric sensors must be addressed first before considering extending their sensitivity to low analyte concentrations. These are, in order of importance, selectivity of the ion-selective membrane to main ion followed by the membrane resistance to parallel processes, such as water ingress to the ISM, light sensitivity, change in temperature, presence of gasses in solution and pH and finally resistance of the ion-selective membrane to fouling. In the future, targeted on-site and on-line environmental sensors should be developed, addressing specific environmental conditions. Thus, ion-selective electrodes should be developed with the intention to be suitable to the operational environmental conditions, rather than looking at universal sensor design validated in the idealized and simple sample matrices.